Association between Affiliate Stigma and Psychological Well-being among Caregivers of Patients with Dementia: A Quantitative Report - Mohammed Rasheedan, Ellin; Vimala, Ramoo; Nor Aziyan, Yahaya; Maw Pin, Tan (Malaysian Journal of Nursing, 2023)
Background: The psychological health of caregivers can have a significant impact on the health of individuals with disabilities. People with disabilities whose caregivers experience depression or lack effective coping mechanisms are likely to experience psychological stress. As a result, the health of caregivers is one of the most significant risk factors for placing a caregiver in an institution. Aim: This study investigates the relationship between affiliate stigma and psychological well-being among caregivers of patients with dementia. Methods: Consecutive caregivers were recruited from a clinic at a teaching hospital and a dementia care centre. Affiliate stigma was measured using the 21-item Affiliate Stigma Scale, and caregivers' psychological well-being was measured using the Scale of Psychological Well-Being. A linear regression model with affiliate stigma was used to estimate the associations. Results: Among the 178 recruited caregivers, income and gender were significantly associated with affiliate stigma, while gender, caregiving duration, and dementia stage were significantly associated with psychological well-being. Affiliate stigma showed a significant negative relationship with psychological well-being. Affiliate stigma was identified as the strongest predictor, which explains 54.3% of the variance in psychological well-being. Conclusion: The negative association between affiliate stigma and psychological well-being reinforces the need for awareness programs aimed at decreasing public stigma towards caregivers of people living with dementia.